2013
DOI: 10.1242/jeb.088849
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrient limitation of cyanobacteria on protease inhibitor production and fitness ofDaphnia magna

Abstract: SUMMARYHerbivore-plant interactions have been well studied in both terrestrial and aquatic ecosystems as they are crucial for the trophic transfer of energy and matter. In nutrient-rich freshwater ecosystems, the interaction between primary producers and herbivores is to a large extent represented by Daphnia and cyanobacteria. The occurrence of cyanobacterial blooms in lakes and ponds has, at least partly, been attributed to cyanotoxins, which negatively affect the major grazer of planktonic cyanobacteria, i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…BM25 originating from Lake Bysjön, Sweden (Schwarzenberger et al., ) was cultivated in a chemostat on cyanophycean medium at 20°C and constant light (50 μE m −2 sec −1 ). This cyanobacterium does neither contain trypsin inhibitors or microcystins but shows a high chymotrypsin inhibition (Schwarzenberger et al., ). The dilution rate was 0.23 day −1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…BM25 originating from Lake Bysjön, Sweden (Schwarzenberger et al., ) was cultivated in a chemostat on cyanophycean medium at 20°C and constant light (50 μE m −2 sec −1 ). This cyanobacterium does neither contain trypsin inhibitors or microcystins but shows a high chymotrypsin inhibition (Schwarzenberger et al., ). The dilution rate was 0.23 day −1 .…”
Section: Methodsmentioning
confidence: 99%
“…For this we fed the Daphnia either with a green alga as control food or with 10% of a single‐strand culture of the cyanobacterium Microcystis sp. BM25 that is known to contain chymotrypsin inhibitors (Schwarzenberger, Sadler, & Von Elert, ). This Microcystis strain originates from one of the lakes (Lake Bysjon, Sweden) that was sampled in this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BM25, originating from Lake Bysjön, Sweden (Schwarzenberger, D'Hondt, et al, 2013), was cultivated in a chemostat (dilution rate 0.23/day) on cyanophyceanmedium at 20°C and constant light (50 µE m −2 s −1 ). This cyanobacterium contains neither trypsin inhibitors nor microcystin but shows a high chymotrypsin inhibition (Schwarzenberger, Sadler, & Von Elert, 2013). Carbon concentrations of the autotrophic food suspensions were estimated from photometric light extinction (470 nm) and from carbon extinction equations previously determined and described in detail by Schwarzenberger et al (2017).…”
Section: Animals and Culturesmentioning
confidence: 99%
“…A handful of studies show the role of nutrients, light, temperature (Rohrlack and Utkilen 2007;Halstvedt et al 2008) and bacteria (Sivonen 1990) on production of bioactive compounds from cyanobacteria. Recently, Schwarzenberger et al (2013)showed that the production of protease inhibitor from Microcystis aeruginosa BM 25 is dependent on nitrogen and phosphorus in the culture medium. However, no study compares the production of protease inhibitors from different cyanobacteria under similar culture conditions.…”
Section: Introductionmentioning
confidence: 99%